Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan di Tempat Kerja - S, Saridawati; Wijaya, Mawar Mariska; Yuniar, Nuning; Hasanah, Tarisa Nurputri; Mefia, Sheilla Yoanisa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Organizational culture plays an important role in shaping employee behavior. As a value system, organizational culture consists of the values and attitudes held by employees, which then become the basis for their behavior and attitudes at work. The relationship between organizational culture and organizational performance is considered capable of determining the organization's ability to face environmental changes, and even directly influences employee performance. The overall performance of an organization basically depends on the performance of each employee in it. To complete the assigned tasks, employees must comply with the standards set by the company. This is important to ensure optimal results are achieved. High performance is the result of consistency in implementing organizational culture. This research aims to determine whether there is an influence between organizational culture and employee performance. The method used by researchers in the sampling process was by distributing a questionnaire consisting of 20 questions to 100 respondents. The research results show that organizational culture has a positive and significant effect on employee performance variables by comparing the t_count > t_table value and the significance value is 0.000, which means <0.05.